"Invalidity" due to chronic bronchitis and emphysema: how real is it?. Issue 11 (November 1985) - Pearce, S J; Posner, V; Robinson, A J; Barton, J R; Cotes, J E
Abstract : Hospital discharges and deaths attributed to chronic bronchitis and emphysema have fallen in recent years while the number of those receiving invalidity benefit for these conditions has remained constant. One hundred and fifty seven such persons were invited to take part in this study, in which the diagnosis, degree of respiratory impairment, and other factors contributing to disability were reviewed. The scope for rehabilitation was considered. One hundred subjects agreed to take part; 96 were men and 70 were over 60 years. In only 67 was the main diagnosis chronic bronchitis and emphysema. There was a bimodal distribution of functional impairment, most being severely disabled, but in 20 the FEV1 was within the normal range. Among these asthma was more common and psychological factors were important. Economic factors contributed to "invalidity, " especially among those with a normal FEV1. For 32 of the 57 who had declined to take part some information was available from hospital records. The findings in this group were similar. There was little scope for rehabilitation in the group as a whole as motivation was poor. Less than half had ever seen a chest physician. Specialist assessment before invalidity benefit is claimed is probably desirable.